Goat and sheep population changes on a Masai group ranch in south-western Kenya, 1978-1986 - Wilson, R.T.; Maki, M. Ole (Elsevier, 1989)
Presents results of a survey undertaken to determine goat and sheep population changes at Elangata Wuas group ranch from 1978 to 1986. Describes owners' attitudes to small ruminant production and their assessment of the suitablility of different years for production.